Electrodeposition of Zinc on Iron Plates in the Presence of N,N-Dimethylurea and Sapindus rarak Rind Extract as Additives - Sal Prima Yudha S; Akhmad Ues; Agus M.H. Putranto; Muhamad Alvin Reagen; Muhammad Adli Afif; Jimmy Askhan; Lenon Jus Pentus Tarigan (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2026)
A study on the addition of natural in the form of Lerak (Sapindus rarak) fruit rinds extract (ESR and synthetic additives in the form of N,N-dimethylurea (DMU) compounds in the zinc electrodeposition process on iron plates was carried out at room temperature. The results of this study show that the electrodeposition of zinc in electrolyte solution treated with Sapindus rarak extract additive gives a more visually uniform and compact coating morphology based on optical microscopy observations coating product than the electrodeposition product without additive or using N,N-dimethylurea additive. This has been observed using the naked eye and supported by observations under an optical microscope. The existence of zinc coating on the surface of the iron plate is supported by an increase in material thickness (control: 0.051 mm), (DMU: 0.025 mm) and (ESR: 0.028 mm) and an increase in material weight (control: 0.085 g), (DMU: 0.074 g) and (ESR: 0.074 g). In conclusion, the addition of DMU and ESR reduced the thickness and mass gain compared with the additive-free control.